2020
DOI: 10.24908/pceea.vi0.14180
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of Entrepreneurship Education at Canadian Engineering Schools – A Representative Overview from EETI SIG Members

Abstract: With the rise of an innovation-based, technology-centric economy over the past two decades, there has been a shift in the market, enabling technological entrepreneurs to build business ventures that have realized accelerated growth and reached considerable scale. This “new economy” has created a need for individuals with a balanced skill set accompanying both business acumen, and technological innovation of complex systems.  In esponse to this need, post-secondary engineering education institutions are teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Teaching entrepreneurship within engineering programs is particularly useful for engineering students for two main reasons. First, as was previously recognized, entrepreneurship education offers "an experiential learning opportunity for students and graduates to practice and demonstrate their twelve (12) attributes defined by the Canadian Engineering Accreditation Board (CEAB)" [3]. Second, while most entrepreneurship programs in Canadian universities are offered by business faculties, engineering is the most common educational undergraduate background of Canadian tech start-up founders across all industries, except for the healthcare sector, where a science degree dominates [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching entrepreneurship within engineering programs is particularly useful for engineering students for two main reasons. First, as was previously recognized, entrepreneurship education offers "an experiential learning opportunity for students and graduates to practice and demonstrate their twelve (12) attributes defined by the Canadian Engineering Accreditation Board (CEAB)" [3]. Second, while most entrepreneurship programs in Canadian universities are offered by business faculties, engineering is the most common educational undergraduate background of Canadian tech start-up founders across all industries, except for the healthcare sector, where a science degree dominates [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the practice of teaching engineering entrepreneurship can be considered to be established in higher education, entrepreneurship education research is still only emerging, in particular within engineering education [3]. More generally, entrepreneurship education research has identified the need to distinguish entrepreneurship education activities based on their purposed goals, commonly labelled as teaching about, for, and through entrepreneurship [5].…”
Section: Introductionmentioning
confidence: 99%
“…The rise of technological innovation-based companies greatly changed the economic developments over the past few decades by commercialization of scientific and technology-driven innovations. As a result, employers and policymakers alike demand more graduates with the mindset and skills to recognize and create innovative entrepreneurship or intrapreneurship opportunities in order to remain competitive [1]. Furthermore, Engineers Canada has identified "entrepreneurship, innovation, and creativity" as one of the five core values for the engineering profession in Canada [2].…”
Section: Introductionmentioning
confidence: 99%